Sensitive Electrochemical Prostate Specific Antigen Aptasensor: Effect of Carboxylic Acid Functionalized Carbon Nanotube and Glutaraldehyde Linker. Issue 5 (13th January 2016) - Tahmasebi, Fatemeh; Noorbakhsh, Abdollah
Abstract: The performance of carboxylic acid functionalized carbon nanotubes (CNTs(COOH) ), chitosan (Chit), carbon nanotubes‐chitosan (CNTs‐Chit and CNTs(COOH) ‐Chit) for immobilizing of amino‐functionalized ssDNA and fabrication of electrochemical prostate specific antigen (PSA) aptasensor were studied in detail using X‐ray diffraction spectroscopy (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT‐IR) and electrochemical impedance spectroscopy (EIS). The assemblies of capture probe are formed on the surface via two approaches: EDC/NHS chemistry and glutaraldehyde linker. Cyclic voltammetry (CV), differential pulse voltammetry (DPV) and EIS techniques were used to investigate the analytical performance of the PSA aptasensor. Under optimum conditions the sensitivity of 0.0026 µA/(ng/ml) and a limit of detection of 0.75 ng/ml (22 pM) were obtained for PSA detection. This protocol offers a new means for sensitive detection of PSA with some advantages in terms of simplicity, selectivity, ease of use and regenerability. Abstract :